Primary cutaneous adenoid cystic carcinoma in the scalp with pulmonary metastases: a case report - Rafael Everton Assunção Ribeiro da Costa; Fergus Tomás Rocha de Oliveira; Eugênio de Sá Coutinho; Carlos Eduardo Coelho de Sá (Sociedade Brasileira de Dermatologia (SBD), 2022)
Primary cutaneous adenoid cystic carcinoma (PCACC) is a rare tumor with an estimated incidence rate of 0.23 cases/1,000,000 people per year. A 60-year-old man presented a scalp lesion in 2017. Initially, it was not possible to perform a histopathologic diagnosis. In 2018, surgical biopsy and immunohistochemistry of the local skin recurrence indicated a diagnosis of PCACC (treatment was surgery and radiotherapy). In 2020, a new local tumor recurred and was surgically resected. The patient had systemic metastases (pulmonary metastases) and underwent chemotherapy. Currently, the pulmonary metastases are stable. The PCACC has progressed to pachymeninges.